Approaching Twitter sociologically: a case study of the public humiliation of HIV-positive women - Sioula-Georgoulea, Ismini (The Greek Review of Social Research, 2015)
The present study examines the online discussion on Twitter regarding the stigmatization of HIV-positive women in Athens in May 2012. The method of critical discourse analysis is applied on the anti-sovereign discourses that were articulated on Twitter, while the incident was taking place. The virtual countersphere is analyzed with regards to its political implications, such as the reproduction of the unfree sovereign discourse and the mobilization towards political action.